Adipocyte-derived CCDC3 promotes tumorigenesis in epithelial ovarian cancer through the Wnt/ß-catenin signalling pathway - Fen Wang; Feng Jin; Shanshan Peng; Chen Li; Li Wang; Shubin Wang (Biochemistry and Biophysics Reports, 2023)
Introduction: Epithelial ovarian cancer (EOC) is a highly aggressive disease whose unique metastatic site is the omentum. Coiled-coil domain containing 3 (CCDC3) is an adipocyte-derived secreted protein that is specifically elevated in omental adipose tissue. However, its function is still unknown. Material and methods: Initially, a Kaplan–Meier plot was applied to evaluate the prognostic value of CCDC3 expression in patients with EOC. A bioinformatics analysis was next used to explore the biological function of CCDC3 in EOC. Western blot, quantitative real-time polymerase chain reaction, and in vitro invasion and migration assays were performed using SKOV3 cells and CCDC3 secreted by rat adipocytes to analyzes the impact of CCDC3 on EOC and the underlying mechanism. Results: Overexpression of CCDC3 was associated with poor prognosis of EOC. CCDC3 interacted with multiple key signalling pathways, including the Wnt/β-catenin pathway. EOC cellular proliferation, migration, and invasion were promoted in vitro when co-cultured with CCDC3 enriched conditioned medium, and this tumour-promoting effect was induced by activating the Wnt/β-catenin pathway. Furthermore, the epithelial-mesenchymal transition of EOC cells was reversed after CCDC3 silencing. Conclusions: Our results support that CCDC3 promotes EOC tumorigenesis through the Wnt/β-catenin pathway and that CCDC3 may serve as a novel prognostic biomarker and therapeutic target for metastatic EOC.